Hubungan Karakteristik Individu dan Lingkungan Sosial Terhadap Perilaku Buang Air Besar Sembarang: HUBUNGAN KARAKTERISTIK INDIVIDU DAN LINGKUNGAN SOSIAL TERHADAP PERILAKU BUANG AIR BESAR SEMBARANG - Hayana Hayana; Hastuti Marlina; Anggun Kurnia (STIKes Hang Tuah Pekanbaru, 2018)
Hygienic behavior that includes the habit or behavior of defecation (BAB). Behavior defecation is considered correct is when residents do it in the toilet. Many villagers in TanjungMedang village who do not have a toilet that is eligible to defecate.Caused Because of lack of information and knowledge of the community so that people do defecate carelessly. This study aims to determine the relationship of education, knowledge, income, habits, attitudes, social support and the role of health officers to behavior open defacation free In TanjungMedang Village, Rangsang District, Kepulauan Meranti Regency in 2017 This research uses Cross Sectional design and using Simple Random Sampling technique. The sample of research as many as 191 people. Measuring tool used in this research is questionnaire and data processing using computerized. Independent variables in this research are education, knowledge, income, habit, attitude, social support and role of health officer. Dependent variable is behavior open defacation free. The analysis used is Univariat and Bivariat with Chi-Square test, The results showed that the knowledge variable (ph = 0.005); Income (p = 0.003); Attitude (p = 0.002); Custom (p = 0.022) related to behavior open defacation free. And educational variables (p = 0.205); Social support (p = 0.267); And the role of health workers (p = 0.103) has no relationship to behavior open defacation free The conclusion of the research is attitude as the dominant factor related to behavior open defacation free To reduce behavior open defacation free Can be run a clean and healthy lifestyle in everyday life by applying it to behave BAB to be able to keep the house always stay clean and healthy